King of the Zoo - Perl, Erica S.; Urbanovic, Jackie (USA, 2013)
Each of the animals at the zoo thinks of himself as King of the Zoo but Carlos the Chameleon is sure that the crown is his, and he has at least one ally...
Keywords: Animal Story; Chameleons; Juvenile Fiction; Zoo Animals